2006
DOI: 10.1300/j015v29n01_06
|View full text |Cite
|
Sign up to set email alerts
|

“Carrying Our Burden in the Heat of the Day”: Mid-Life Self-Sacrifice Within the Family Circle Among Black Professional Women

Abstract: The following article examines both the cultural and bi-cultural complexities of self-sacrifice as a major familial and communal demand experienced by African American 1 professional women at mid-life. As a prelude to this clinical discussion, an examination of the sociological, cultural and inter-cultural dimensions of self-sacrifice are provided. To support clinical intervention and self help, a series of conceptual models, and problem solving and assessment tools are presented to aid practitioners in delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In this study, navigating a lack of resources and opportunities was reported to be an important component that affected the participants’ stress. Consistent with research (Johnson, 2010; King & Ferguson, 2006), Black women may experience poverty-induced stressors based on access to economic wealth and social resources. Previous research notes that socioeconomic status (class) intersects with race and gender (Jerald et al, 2017; Thomas et al, 2008).…”
Section: Discussionsupporting
confidence: 67%
“…In this study, navigating a lack of resources and opportunities was reported to be an important component that affected the participants’ stress. Consistent with research (Johnson, 2010; King & Ferguson, 2006), Black women may experience poverty-induced stressors based on access to economic wealth and social resources. Previous research notes that socioeconomic status (class) intersects with race and gender (Jerald et al, 2017; Thomas et al, 2008).…”
Section: Discussionsupporting
confidence: 67%
“…Many people feel they need to sacrifice to care for themselves (Dollahitte et al, 2009; Impett et al, ). King and Ferguson () suggested self‐care techniques to help Black women redefine their roles so that their levels of sacrifice could be more manageable. These techniques may be useful to women of other ethnicities and men with similar struggles.…”
Section: Background Literaturementioning
confidence: 99%